Evaluating User Experience in Games Concepts and Methods - Bernhaupt, Regina (Human-Computer Interaction Series, 2010)
User Experience has become a major research area in human-computer interaction. The area of game design and development has been focusing on user experience evaluation for the last 20 years, although a clear definition of user experience is still to be established. The contributors to this volume explore concepts that enhance the overall user experience in games such as fun, playability, flow, immersion and many others. Presenting an overview of current practice from academia and industry in game development, the book shows a variety of methods that can be used to evaluate user experience in games, not only during game-play but also before and after the game play. Evaluating User Experiences in Games: Presents a broad range of user experience evaluation methods and concepts; Provides insights on when to apply the various user experience evaluation methods in the development cycle and shows how methods can be also applied to a more general HCI context; Includes new research on evaluating user experience during game play and after; and social play; Describes new evaluation methods; Details methods that are also applicable for exertion games or tabletop games. This comprehensive book will be welcomed by researchers and practitioners in the field.